2017
DOI: 10.1021/acs.iecr.6b04773
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Volumetric Properties Using Refractive Index Measurements for Nonpolar Hydrocarbons and Crude Oils

Abstract: A novel method to evaluate volumetric properties, namely the thermal expansivity (α P ) and the isothermal compressibility (κ T ) for nonpolar hydrocarbon systems using refractive index measurements, is presented in this work. New expressions for α P and κ T are derived from the Lorentz–Lorenz equation and the One-Third rule, respectively. A further simplified expression for α P is proposed requiring only refractive index data and molecular weight for calculation. Densities and refractive indices of 12 pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Experimental density data are available for various pure hydrocarbons at temperatures in the range of 283−343 K and ambient pressure. 37 Experimental data for the derivative properties of n-heptane, n-dodecane, benzene, and toluene are taken from NIST REFPROP. 38 A summary of the pure component experimental data used in this section is shown in Table 3.…”
Section: Modeling Of High-pressure Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental density data are available for various pure hydrocarbons at temperatures in the range of 283−343 K and ambient pressure. 37 Experimental data for the derivative properties of n-heptane, n-dodecane, benzene, and toluene are taken from NIST REFPROP. 38 A summary of the pure component experimental data used in this section is shown in Table 3.…”
Section: Modeling Of High-pressure Andmentioning
confidence: 99%
“…Parity plots for density modeling of pure components using PC-SAFT parametrized by ASV correlations. Experimental data are at 1 bar and 283–343 K taken from Wang et al …”
Section: Modeling Of High-pressure and High-temperature Volumetric Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of the newly developed ARI for well-defined mixtures is studied in this section. Three binary and three ternary hydrocarbon mixtures are studied with mixture data taken from the work of Wang et al The properties of the six mixtures are shown in Table . The reader is referred to ref for more information about the experimental procedure and properties of the hydrocarbons used.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of Binary and Ternary Mixtures Used for This Investigation. The Calculated ARI Is Based on the Hydrocarbon Mixtures Being Treated as Lumped Solvents 23. …”
mentioning
confidence: 99%